EFEKTIVITAS QARDH AL-HASAN DALAM KERANGKA ZAKAT PRODUKTIF UNTUK PEMBERDAYAAN UMKM - Fauzi Rizal (Ekonomi Islam, 2022)
Diversity in living conditions Is an inevitability in this world and poverty is a serious problem that must be solved. Criminality and the tragedy of theft cannot be separated from the problem of poverty. In the midst of this problem, zakat is a solutive step to solve the problem of economic inequality in the midst of the community. In addition to zakat as a command from Allah SWT, it is also a "socioeconomic" function within the framework of mutual cooperation between fellow humans. This study aims to determine the potential of productive zakat and effectively reduce the redistribution of productive zakat funds for the participation of small businesses. This paper is a literature study using a grounded teory approach with the SLR method aimed at describing and critically analyzing productive zakat as an instrument of community empowerment and synthesizing the results of previous research. This paper, in addition to describing zakat from all its demensions, also explains zakat as a solution to poverty with the effectiveness of the concept of productive zakat through the qardh al-hasan agreement. The results of this study are the effectiveness of productive zakat with qardh al-hasan agreements in each zakat institution is different, some are carried out as expected and assisted small businesses get a decent life and some places still do not meet expectations because of several obstacles that must be evaluated. Finally, the efforts of the qardh al-hasan contract in productive zakat to realize the life of the fostered small businesses for the better, the qardh al-hasan contract should be used for tatawwu' contracts, not as commercial transactions. Keywords: Effectiveness, Productive Zakat, Qardh Al-Hasan, Small Businesses.